The role of heterotrophic plate count bacteria in bottled water quality assessment. (March 2016) - Diduch, Malwina; Polkowska, Żaneta; Namieśnik, Jacek
Abstract: The ever-growing popularity of bottled water is the result of many factors. One of the most relevant is the widespread belief that bottled water is safer for drinking than tap water. In fact many literature sources describe the rapid growth of the amounts of microorganisms in bottled water samples following the bottling process. The main purpose of this article is to collect the information on the factors which may affect this phenomenon and to assess the suitability of the existing microbiological requirements for this type of products in the context of consumer health protection. Highlights: This paper reviews the relevant literature on HPC bacteria in bottled water samples. Factors may affect on growth of the numbers of microorganisms in bottled waters and impact the HPC numbers on health risk was described.